ANALYSIS OF THE CIVIL DECISION EXECUTION MECHANISM IN THE INDONESIAN JUDICIAL SYSTEM - Divani Tsamara Madiyya; Naurah Alfi Mufidah Anwar; Amandha Ayu Bunga Syabina; Nazwa Wahdatul Hilaliyah; Kesya Putri Kuswara; Frederika Eugene; Carolyn Victoria; Yuni Priskila Ginting (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The last phase that assesses the efficiency of law enforcement in the Indonesian legal system is the execution of civil decisions. Despite having a solid legal foundation thanks to the Reglement Buitengewesten (RBg) and the Herzien Inlandsch Reglement (HIR), its execution frequently encounters a number of challenges. The purpose of this study is to examine how civil judgments are carried out, including the legal foundation, several forms of execution (such as real, payment of money, and vacating), stages of implementation (such as aanmaning, execution seizure, and forceful execution), and practical challenges. Normative juridical study using a conceptual and statutory approach is the methodology employed. The study's findings show that the primary causes of execution failure are non-legal barriers like social opposition and a lack of official backing, as well as legal barriers like verzet, derden verzet, and ambiguous verdicts. Effective, efficient, and equitable execution of civil judgments requires systemic change and interagency cooperation.